Thực hiện phép tính
A = (\(\sqrt{x}\)- 1/2) (\(\sqrt{x}\)+ 1/2) (4x - 1)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\dfrac{12}{1+\sqrt{5}}+\dfrac{15}{\sqrt{5}}-\dfrac{\sqrt{20}-5}{2-\sqrt{5}}\)
=\(\dfrac{12\left(1-\sqrt{5}\right)}{-4}+\dfrac{15\sqrt{5}}{5}-\dfrac{\left(\sqrt{20}-5\right)\left(2+\sqrt{5}\right)}{-1}\)
=\(-3+3\sqrt{5}-\sqrt{5}+3\sqrt{5}+4\sqrt{5}+10-10-5\sqrt{5}\)
=\(5\sqrt{5}-3\)
b)\(\dfrac{2\sqrt{x}}{\sqrt{x}-1}-\dfrac{3x}{x-\sqrt{x}}+\dfrac{1}{\sqrt{x}}\)
=\(\dfrac{2x-3x+\sqrt{x}-1}{\sqrt{x}\left(\sqrt{x}-1\right)}\)
=\(\dfrac{-x+\sqrt{x}-1}{\sqrt{x}\left(\sqrt{x}-1\right)}\)
1:
a: \(\sqrt{36}-\sqrt{100}=6-10=-4\)
b: Để \(\sqrt{\dfrac{2}{2x-1}}\) có nghĩa thì \(\dfrac{2}{2x-1}>=0\)
=>2x-1>0
=>x>1/2
2:
a: \(A=\dfrac{\left(15\sqrt{180}-5\sqrt{200}-3\sqrt{450}\right)}{\sqrt{10}}\)
\(=15\sqrt{\dfrac{180}{10}}-5\sqrt{\dfrac{200}{10}}-3\sqrt{\dfrac{450}{10}}\)
\(=15\sqrt{18}-5\sqrt{20}-3\sqrt{45}\)
\(=45\sqrt{2}-10\sqrt{5}-9\sqrt{5}\)
\(=45\sqrt{2}-19\sqrt{5}\)
b: \(B=\sqrt{32}-\sqrt{50}-16\sqrt{\dfrac{1}{8}}\)
\(=4\sqrt{2}-5\sqrt{2}-\dfrac{16}{\sqrt{8}}\)
\(=-\sqrt{2}-2\sqrt{8}=-\sqrt{2}-4\sqrt{2}=-5\sqrt{2}\)
\(a,\dfrac{3}{5}-\dfrac{1}{2}\sqrt{1\dfrac{11}{25}}=\dfrac{3}{5}-\dfrac{1}{2}\sqrt{\dfrac{36}{25}}=\dfrac{3}{5}-\dfrac{1}{2}.\dfrac{\sqrt{6^2}}{\sqrt{5^2}}=\dfrac{3}{5}-\dfrac{1}{2}.\dfrac{6}{5}=\dfrac{3}{5}-\dfrac{6}{10}=\dfrac{3}{5}-\dfrac{3}{5}=0\)
\(b,\left(5+2\sqrt{6}\right)\left(5-2\sqrt{6}\right)=5^2-\left(2\sqrt{6}\right)^2=25-2^2.\sqrt{6^2}=25-4.6=25-24=1\)
\(c,\sqrt{\left(2-\sqrt{3}\right)^2}+\sqrt{4-2\sqrt{3}}\\ =\left|2-\sqrt{3}\right|+\sqrt{\sqrt{3^2}-2\sqrt{3}+1}\\ =2-\sqrt{3}+\sqrt{\left(\sqrt{3}-1\right)^2}\\ =2-\sqrt{3}+\left|\sqrt{3}-1\right|\\ =2-\sqrt{3}+\sqrt{3}-1\\ =1\)
\(d,\dfrac{\left(x\sqrt{y}+y\sqrt{x}\right)\left(\sqrt{x}-\sqrt{y}\right)}{\sqrt{xy}}\left(dk:x,y>0\right)\\ =\dfrac{\left(\sqrt{x^2}.\sqrt{y}+\sqrt{y^2}.\sqrt{x}\right)\left(\sqrt{x}-\sqrt{y}\right)}{\sqrt{xy}}\\ =\dfrac{\sqrt{xy}\left(\sqrt{x}+\sqrt{y}\right)\left(\sqrt{x}-\sqrt{y}\right)}{\sqrt{xy}}\\ =\sqrt{x^2}-\sqrt{y^2}\\ =\left|x\right|-\left|y\right|\\ =x-y\)
1.
\(\sqrt{50}-3\sqrt{8}+\sqrt{32}=5\sqrt{2}-6\sqrt{2}+4\sqrt{2}=3\sqrt{2}\)
2.
a, ĐK: \(x\in R\)
\(pt\Leftrightarrow\sqrt{\left(x-2\right)^2}=1\)
\(\Leftrightarrow\left|x-2\right|=1\)
\(\Leftrightarrow\left[{}\begin{matrix}x-2=1\\x-2=-1\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=3\\x=1\end{matrix}\right.\)
b, ĐK: \(x\ge3\)
\(pt\Leftrightarrow\sqrt{x-3}\left(\sqrt{x}-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}\sqrt{x-3}=0\\\sqrt{x}-1=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=3\left(tm\right)\\x=1\left(l\right)\end{matrix}\right.\)
a, \(A=2\sqrt{3}-\sqrt{12}-\sqrt{9}\)
\(=2\sqrt{3}-2\sqrt{3}-3=-3\)
b, \(B=\sqrt{3}\left(\sqrt{12}+\sqrt{27}\right)\)
\(=\sqrt{3}\left(2\sqrt{3}+3\sqrt{3}\right)\)
\(=\sqrt{3}.5\sqrt{3}=5.3=15\)
Bài 1:
a: \(\sqrt{252}-\sqrt{700}+\sqrt{1008}-\sqrt{448}\)
\(=6\sqrt{7}-10\sqrt{7}+12\sqrt{7}-8\sqrt{7}\)
\(=8\sqrt{7}\)
Bài 3:
a: \(\sqrt{27^2-23^2}=10\sqrt{2}\)
b: \(\sqrt{37^2-35^2}=12\)
c: \(\sqrt{65^2-63^2}=16\)
d: \(\sqrt{117^2-108^2}=45\)
`a)1/[x-5x^2]-[25x-15]/[25x^2-1]`
`=[-(5x+1)-x(25x-15)]/[x(5x-1)(5x+1)]`
`=[-5x-1-25x^2+15x]/[x(5x-1)(5x+1)]`
`=[-25x^2+10x-1]/[x(5x-1)(5x+1)]`
`=[-(5x-1)^2]/[x(5x-1)(5x+1)]`
`=[1-5x]/[x(5x+1)]`
________________________________________________-
`b)(-1/[x^2-4x]+2/[16-x^2]-[-1]/[4x+16]):1/[4x]`
`=[-4(x+4)-8x+x(x-4)]/[4x(x-4)(x+4)].4x`
`=[-4x-16-8x+x^2-4x]/[(x-4)(x+4)]`
`=[x^2-16x-16]/[x^2-16]`
a: \(\dfrac{3}{\sqrt{2}}+\sqrt{\dfrac{1}{2}}-2\sqrt{18}+\sqrt{\left(1-\sqrt{2}\right)^2}\)
\(=\dfrac{3}{2}\sqrt{2}+\dfrac{1}{2}\sqrt{2}-2\cdot3\sqrt{2}+\left|1-\sqrt{2}\right|\)
\(=2\sqrt{2}-6\sqrt{2}+\sqrt{2}-1=-3\sqrt{2}-1\)
b: \(\dfrac{1}{\sqrt{3}}+\dfrac{1}{3\sqrt{2}}+\dfrac{1}{\sqrt{3}}\cdot\dfrac{\sqrt{3}-\sqrt{2}}{2\sqrt{3}}\)
\(=\dfrac{1}{\sqrt{3}}+\dfrac{1}{\sqrt{18}}+\dfrac{\sqrt{3}-\sqrt{2}}{12}\)
\(=\dfrac{4\sqrt{3}+2\sqrt{2}+\sqrt{3}-\sqrt{2}}{12}\)
\(=\dfrac{5\sqrt{3}+\sqrt{2}}{12}\)
c: \(\sqrt[3]{\dfrac{3}{4}}\cdot\sqrt[3]{\dfrac{9}{16}}=\sqrt[3]{\dfrac{3}{4}\cdot\dfrac{9}{16}}=\sqrt[3]{\dfrac{27}{64}}=\dfrac{3}{4}\)
d: \(\dfrac{\sqrt[3]{54}}{\sqrt[3]{-2}}=\sqrt[3]{\dfrac{54}{-2}}=-\sqrt[3]{27}=-3\)
e: \(\sqrt[3]{5\sqrt{2}+7}-\sqrt[3]{5\sqrt{2}+7}=0\)
a: Ta có: \(\left(\dfrac{\sqrt{6}-\sqrt{2}}{1-\sqrt{3}}-\dfrac{5}{\sqrt{5}}\right):\dfrac{1}{\sqrt{5}-\sqrt{2}}\)
\(=-\left(\sqrt{5}+\sqrt{2}\right)\left(\sqrt{5}-\sqrt{2}\right)\)
=-5+2
=-3
\(A=\left(\sqrt{x}-\frac{1}{2}\right)\left(\sqrt{x}+\frac{1}{2}\right)\left(4x-1\right)\)
\(A=\sqrt{x^2}-\left(\frac{1}{2}\right)^2.\left(4x-1\right)\)
\(A=x-\frac{1}{4}\left(4x-1\right)\)
\(A=x-x+\frac{1}{4}\)
\(A=\frac{1}{4}\)
@Cừu
Trả lời:
\(A=\left(\sqrt{x}-\frac{1}{2}\right)\left(\sqrt{x}+\frac{1}{2}\right)\left(4x-1\right)\)
\(=\left[\left(\sqrt{x}\right)^2-\left(\frac{1}{2}\right)^2\right]\left(4x-1\right)\)
\(=\left(x-\frac{1}{4}\right)\left(4x-1\right)\)
\(=4x^2-x-x+\frac{1}{4}\)
\(=4x^2-2x+\frac{1}{4}\)